Combining ability of black common bean developed under a biological nitrogen fixation system - Nayana Valéria Costa; Patrícia Guimarães Santos Melo; Helton Santos Pereira; Enderson Petrônio de Brito Ferreira; Adriano Moreira Knupp; Leonardo Cunha Melo (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to select parents and segregating populations of black common bean developed under a biological nitrogen fixation system. Twenty-eight segregating populations were obtained from complete diallel crosses among eight parents with black grains, a high yield, and a high potential for biological fixation. The segregating populations were evaluated for grain yield and 100-grain weight in four environments, where the main source of nitrogen was rhizobial inoculation. The diallel analysis indicated a predominance of additive effects for 100-grain weight and of nonadditive effects for grain yield. Parents 'BRS FP403', CNFP 15188, and 'BRS Esteio' showed the highest general combining ability estimates for 100-grain weight, whereas parents 'BRS Esplendor' and CNFP 15310 were the most suitable for forming populations with a higher yield in biological fixation systems. The 'BRS FP403'/'BRS Esplendor' and 'BRS FP403'/CNFP 15310 populations combined good mean estimates and specific combining ability for both evaluated traits, which makes them promising for the extraction of superior lines for cultivation in production systems without chemical nitrogen fertilization and with nitrogen supply predominantly through biological fixation.